Value of 100 kVp scan with sinogram-affirmed iterative reconstruction algorithm on a single-source CT system during whole-body CT for radiation and contrast medium dose reduction: an intra-individual feasibility study. Issue 2 (February 2018) - Nagayama, Y.; Nakaura, T.; Oda, S.; Tsuji, A.; Urata, J.; Furusawa, M.; Tanoue, S.; Utsunomiya, D.; Yamashita, Y.
Abstract : Aim: To perform an intra-individual investigation of the usefulness of a contrast medium (CM) and radiation dose-reduction protocol using single-source computed tomography (CT) combined with 100 kVp and sinogram-affirmed iterative reconstruction (SAFIRE) for whole-body CT (WBCT; chest–abdomen–pelvis CT) in oncology patients. Materials and methods: Forty-three oncology patients who had undergone WBCT under both 120 and 100 kVp protocols at different time points (mean interscan intervals: 98 days) were included retrospectively. The CM doses for the 120 and 100 kVp protocols were 600 and 480 mg iodine/kg, respectively; 120 kVp images were reconstructed with filtered back-projection (FBP), whereas 100 kVp images were reconstructed with FBP (100 kVp-F) and the SAFIRE (100 kVp-S). The size-specific dose estimate (SSDE), iodine load and image quality of each protocol were compared. Results: The SSDE and iodine load of 100 kVp protocol were 34% and 21%, respectively, lower than of 120 kVp protocol (SSDE: 10.6±1.1 versus 16.1±1.8 mGy; iodine load: 24.8±4versus 31.5±5.5 g iodine, p< 0.01). Contrast enhancement, objective image noise, contrast-to-noise-ratio, and visual score of 100 kVp-S were similar to or better than of 120 kVp protocol. Conclusion: Compared with the 120 kVp protocol, the combined use of 100 kVp and SAFIRE in WBCT for oncology assessment with an SSCT facilitated substantial reduction in the CM and radiation dose while maintaining image quality. Highlights: 100 kVp scans enable a 20% iodine load reduction while preserving sufficient organ contrast. SAFIRE yields a 34% radiation dose reduction without increasing image noise. Quality of 100 kVp images used with SAFIRE is equivalent to that of 120 kVp images. This approach is useful for clinical oncology assessments using single-source CT.